(3TQM GdYQhV dGHf GdSbGWs - (3CHhGdMSf Hf HQjs; (3GHf GdSbGW , CHh YHO Gddgs ((3CHhHcQ eMeO Hf CMeO Hf eMeO Hf eMeO Hf YHOGddg GdaGSj s)
(3ChdgG (B:s
(3CeG HYO aEfi GSJNQJ Gddg SHMGfg hGSJYfJg aj hVY TQM Ydi oeNJUQ CHj YHOGddg Hf GdSbGW s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddg hMSf Yhfg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B6s
Keywords: (3GdYQhV hGdbhGais